Polyethyleneimine (PEI) Functionalized Metal Oxide Nanoparticles Recovered From the Catalytic Converters of Spent Automotive Exhaust Systems and Application for CO2 Adsorption - Irani, Vahid; Khosh, Akram Ghanbari; Tavasoli, Ahmad (Frontiers in Energy Research, 2020)
A novel CO2 sorbent was prepared from the catalytic converters of spent automotive exhaust system by modifying with polyethyleneimine (PEI) through wet impregnation method. The prepared sorbent was characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), thermogravimetric analysis (TGA), X-ray diffraction (XRD) and Brauer-Emmett-teller (BET) analysis before and after functionalization. Different PEI loadings were employed to study the adsorption performance of as-prepared sorbent. The characterization results showed no significant change in the structure, but the surface area was decreased after modification with amine groups. The adsorption was remarkably improved by increasing the PEI loading. The optimal PEI loading on the as-prepared sorbent was 60 wt.%. At optimal PEI loading, the CO2 adsorption reached to 101.3 mg (g sorbent)–1 at 70°C and partial pressure of 100 kPa. Further PEI loading had a negative effect on the adsorption. The CO2 adsorption capacity increased to 125.2 mg (g sorbent) –1 in the presence of 1 vol.% of the H2O moisture. Results confirmed the high performance of novel sorbent compared to other porous sorbents such as carbon-based materials. Adsorption/desorption cycles revealed that the PEI-impregnated sorbent can be satisfactorily regenerated after CO2 adsorption process.